2018
DOI: 10.3390/ijerph15112364
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Toxic Element Pollution Levels and Risk Assessment of Soils and Sediments in the Upstream River, Miyun Reservoir, China

Abstract: This study focused on the Chao River and Baimaguan River located upstream of the Miyun Reservoir in Miyun District (Beijing, China). Soil and sediment samples were collected from the river and drainage basin. Total nitrogen, total phosphorus, and six potentially toxic elements including cadmium, zinc, lead, chromium, arsenic, and copper, were analyzed in terms of concentration, potential ecological risk, and human health risk. The average concentrations of the six potentially toxic elements were all below the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…PTEs cause adverse ecological effects on plants and organisms such as impacting their activity, growth rate/yield, metabolism and reproduction, causing symptoms of physiological stress and potentially death. The extent of the adverse effect depends on the exposure route (ingestion, dermal absorption or uptake of pore water) and time, resistance (related to residence time of the PTEs in the environment) and detoxification mechanisms of the plant or animal (Alloway, 2013;Eggleton and Thomas, 2004;Ehlers and Loibner, 2006;Hooda, 2010;Pan et al, 2018;Shahid et al, 2017;Winger et al, 1998). Leaching of PTEs from the floodplain soil into the groundwater or river will also cause adverse effects to aquatic organism in these environments (Zia et al, 2018).…”
Section: Ptes In Floodplain Soilmentioning
confidence: 99%
“…PTEs cause adverse ecological effects on plants and organisms such as impacting their activity, growth rate/yield, metabolism and reproduction, causing symptoms of physiological stress and potentially death. The extent of the adverse effect depends on the exposure route (ingestion, dermal absorption or uptake of pore water) and time, resistance (related to residence time of the PTEs in the environment) and detoxification mechanisms of the plant or animal (Alloway, 2013;Eggleton and Thomas, 2004;Ehlers and Loibner, 2006;Hooda, 2010;Pan et al, 2018;Shahid et al, 2017;Winger et al, 1998). Leaching of PTEs from the floodplain soil into the groundwater or river will also cause adverse effects to aquatic organism in these environments (Zia et al, 2018).…”
Section: Ptes In Floodplain Soilmentioning
confidence: 99%
“…It confirmed that mining activity was the major source of Pb pollution in soils. This phenomenon is mainly due to the considerable contribution of long-term frequent mining activities, ore mining and smelting, and abundant small-scale mines distributed in the upper area of the Miyun Reservoir; therefore, most soil Pb likely represents locally emitted Pb [27,30,33,62]. In contrast, natural background sources are an important source of Pb in sediments.…”
Section: Pb Isotope Ratios and Source Apportionmentmentioning
confidence: 99%
“…Potentially toxic elements (PTEs), including trace elements and heavy metals, are naturally occurring substances in the environment; however, the anthropogenic activities in some regions have increased their concentration [1,2]. Due to their bioaccumulation capacity, persistent nature, and toxicity, some PTEs are considered priority pollutants [3].…”
Section: Introductionmentioning
confidence: 99%